Comparing the efficacy of teriparatide and bisphosphonates in osteoporotic patients undergoing thoracolumbar spinal fusion: a meta-analysis - Ji, Xinghua; Duan, Jinhui; He, Guoyu; Wang, Junjie; Xing, Zejun (Frontiers in Surgery, 2025)
ObjectivesThis study compared the efficacy of teriparatide and bisphosphonates(BPs) in osteoporotic patients who underwent thoracolumbar spinal fusion through a comprehensive meta-analysis of published data from randomized controlled trials and other types of comparative studies.MethodsMajor online databases, including PubMed, EMBASE, Web of Science, and Cochrane Central, were searched for studies on the efficacy of teriparatide and BPs in patients treated with thoracolumbar spinal fusion. Studies that evaluated bone union conditions and other subjective or objective outcomes were included. The publication period ranged from database inception to June 13, 2025.ResultsUltimately, 6 articles with 329 patients were included in this meta-analysis. Compared with BPs, teriparatide had advantages in terms of improving the bone union rate at both the 6-month and 1-year follow-ups and reducing the Oswestry Disability Index (ODI) and leg pain visual analogue scale (VAS) score at the 1-year follow-up. The screw loosening rate, VAS score for low back pain at the 1-year follow-up and ODI score at the 6-month follow-up were not clearly different between the teriparatide and BP groups.ConclusionIn patients undergoing thoracolumbar spinal fusion, compared with BPs, teriparatide clearly promotes bone fusion and improves quality of life, with high safety. However, the small number of studies included in this meta-analysis (six) may have influenced the results in the forest plots.